Dinamika Agraria Nasional dan Sengketa Tanah Adat dalam Perspektif Hukum Kontemporer - Nisa, Ayu Chairun; Asriyani, Arini (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2025)
This study positions customary land not merely as an object of agrarian law but as a reflection of the complex relationship between state entities, local traditions, and the human rights of indigenous communities, which are constantly adapting to the demands of modernisation and the need for legal certainty. Using a normative legal approach and socio-legal analysis, the discourse on the existence and protection of customary rights in Indonesia illustrates the contestation between formal recognition dominated by the national registration system and local practices that still rely on customary values, structures, and legitimacy. This dynamic demands strengthening legal harmonization mechanisms, innovation in institutional instruments, and sensitivity to state policies so that substantive justice and social sustainability for indigenous communities can be realised within the framework of national agrarian law.